Studying Religion Through the Internet among Millennial Muslims: Causes and Consequences - Affan, Muhammad; Thohir, Ajid (FIKRAH, 2020)
This article will discuss the issue of studying religion through the internet as a new trend among Indonesian Millennial Muslims. This study aims to explain the causes and consequences that can arise from this phenomenon. The results of this study are expected to contribute thoughts in the discourse on Islamic Studies in Era 4.0 which is full of disruption. The method used in the study is library research methods. From the studies conducted, it was concluded that this phenomenon emerged as an impact of the rapid development of information and communication technology. The positive side of this phenomenon is efficiency in religious learning. However, this phenomenon also raises the negative side of the threat of religious radicalism content infiltration that is also spread online. So that, caution is needed in interpreting this phenomenon which has become a trend not only in Indonesia but also throughout the world